Trios Lidisi Veneer, Transforming Smiles Using an Intraoral Scanner - A Case Report - Laxmi Pandey; Akanksha Bhatt; Praveen Singh Samant; Jaya Singh (Wolters Kluwer Medknow Publications, 2024)
Introduction: The need to perform restorations with a natural appearance is one of the most challenging aspects of dentistry, and reproducing the colour of natural teeth in restorations is a clinical challenge due to the complex optical characteristics of dentition. Various procedures have been advocated in the literature to correct dental anomalies, particularly in the aesthetic region, such as tooth discoloration due to fluorosis or dentition spacing due to changes in tooth shape, such as peg laterals. Clinical Applications: Veneer are one of the most commonly used treatment modalities in such cases. As the use of ceramics necessitates the use of more opaque restorative materials or different thickness, obtaining adequate results in terms of the final colour of the restoration becomes increasingly difficult. The purpose of this study is to present a clinical case of smile rehabilitation in the anterior region with facets made of lithium disilicate, with the goal of achieving colour uniformity and demonstrating the benefits and achieving smile aesthetics. Take-away Lessons: Technological advancement such as intraoral scanner for impression making have significant improved the success of prosthesis. This case report presents conservative and aesthetic procedure in the management of closing the space in maxillary anterior region using lithium disilicate laminate veneers with trios software.